Assessment of adult body composition using bioelectrical impedance: comparison of researcher calculated to machine outputted values. Issue 1 (7th January 2016) - Franco-Villoria, Maria; Wright, Charlotte M; McColl, John H; Sherriff, Andrea; Pearce, Mark S; ,
Abstract : Objectives: To explore the usefulness of Bioelectrical Impedance Analysis (BIA) for general use by identifying best-evidenced formulae to calculate lean and fat mass, comparing these to historical gold standard data and comparing these results with machine-generated output. In addition, we explored how to best to adjust lean and fat estimates for height and how these overlapped with body mass index (BMI). Design: Cross-sectional observational study within population representative cohort study. Setting: Urban community, North East England Participants: Sample of 506 mothers of children aged 7–8 years, mean age 36.3 years. Methods: Participants were measured at a home visit using a portable height measure and leg-to-leg BIA machine (Tanita TBF-300MA). Measures: Height, weight, bioelectrical impedance (BIA). Outcome measures: Lean and fat mass calculated using best-evidenced published formulae as well as machine-calculated lean and fat mass data. Results: Estimates of lean mass were similar to historical results using gold standard methods. When compared with the machine-generated values, there were wide limits of agreement for fat mass and a large relative bias for lean that varied with size. Lean and fat residuals adjusted for height differed little from indices of lean (or fat)/height 2 . Of 112 women with BMI >30 kg/m 2, 100 (91%) also had high fat, but of the 16 with low BMI (<19 kg/m 2 ) only 5 (31%) also had low fat. Conclusions: Lean and fat mass calculated from BIA using published formulae produces plausible values and demonstrate good concordance between high BMI and high fat, but these differ substantially from the machine-generated values. Bioelectrical impedance can supply a robust and useful field measure of body composition, so long as the machine-generated output is not used.